Production Activity Essence and Producer’s Role in the Field of Project Management in the Creative Industries - Proskurina, Mariia; Nikitina, Veronika (Socio-Cultural Management Journal, 2023)
Introduction. The emergence of the cultural and creative industries market as a full-fledged business sector has given rise to new mechanisms for interaction between business entities in the cultural sector. This led to the emergence of a new type of manager – the producer. Its emergence in the cultural sphere necessitated a theoretical understanding of the production activity essence. However, today there is no single definition of the terms “producer” and “production”, and no coherent system of understanding the essence of production as a special type of management activity. Purpose and methods. The purpose of the article is to provide a comprehensive analysis of the essence of production activity and the role of a producer in the field of project management in the creative industries. The theoretical and methodological basis of the study is the principles of the project app-roach to management and their implementation in the field of cultural economy and creative industries. Results. The essence and content of production activity in the context of creative project management are revealed. The article analyses the areas of producers’ responsibility and their hierarchy in the organisational structure of a creative project. The list of personal qualities and professional competences of the producer is studied and recorded. Conclusions. The scientific novelty of the obtained results lies in the clarification of the production activity essence and the producer’s role in the organisation of creative cultural and artistic projects and processes. The significance of the research results lies in the fact that they can be used in the educational process when developing a list of competencies and standards for the speciality “producer of creative projects” and curricula.